DON RIGOBERTO’S SEXUAL FANTASY IN MARIO VARGAS LLOSA IN PRAISE OF THE STEPMOTHER (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
DON RIGOBERTO’S SEXUAL FANTASY IN MARIO VARGAS LLOSA IN PRAISE OF THE STEPMOTHER Dinda Anisa Larasati English Department, Language and Arts Faculty, State University of Surabaya dinda_kdy@yahoo.com Drs. Much. Khoiri M.Si. English Department, Language and Arts Faculty, State University of Surabaya much_choiri@yahoo.com Abstract Sexuality is seen as sinful thing which influences Christian to behave and act based on the society role. Some people tend to repress their sexual fantasy because sexual fantasy is a genre that can lend itself very easily to the sexual elements of life, the depraved, the debauched, or the downright saucy and controversial. The aim of this study is to describe how Don Rigoberto’s sexual fantasy depicted in Mario Vargas Llosa In Praise of the Stepmotherand and to reveal how Don Rigoberto’s sexual fantasy can impact on his wife. The data are in the form of quotation, fragments, and dialogues or monologues that indicated the thoughts and action concerning form of sexual fantasy.The data is applying the theory of fantasy by Jacques Lacan and supported with Baron. This study also uses the concept of anxiety and psychological trauma. Initially, Don Rigoberto obsessed with three things: Physical Hygiene, sex with his wife, and erotic paintings. He devotes a day a week for the care of a different member or organ.His love life with Lucrecia in a world more imaginary than real, of what he wishes she were than what she really is. He always lost in his dream which is imagined erotically things from some media and those can support his sexual fantasy. Don Rigoberto forced his wife (to have) sex with another man which can be deeply shocking for her. Those facts are proof that Don Rigoberto get his satisfaction from his obsession. Keywords: sexuality, fantasy, desire, anxiety, psychological trauma Abstrak Seksualitas dipandang sebagai hal yang berdosa yang mempengaruhi Kristen untuk bersikapdanbertindak berdasarkan peran masyarakat. Beberapa orang cenderung untuk menekan fantasi seksual mereka karena fantasi seksual adalah genre yang dapat menjatuhkan diri seseorang ke dalam unsur-unsurseksualkehidupan, buruk, yang tidak bermoral, dan kontroversial. Tujuan dari skripsi ini adalah untuk menggambarkan bagaimana fantasi seksual Don Rigoberto yang digambarkan di Mario Vargas Llosa In Praise of the Stepmother dan mengungkapkan bagaimana fantasi seksual Don Rigoberto yang berdampak pada istrinya. Di dalam data tersebut terdapat kutipan, fragmen, dan dialog atau monolog yang menunjukkan pemikiran dan tindakan mengenai bentukfantasi. Untuk data seksual menerapkan teori fantasi dari Jacques Lacan dan didukung dengan Baron. Analisis ini juga menggunakan konsep anxiety dan psychological trauma. Pada awalnya, Don Rigoberto terobsesi dengan tiga hal: Fisik higienis, seks dengan istrinya, dan lukisan erotis. Dia menjadikan satu hari dalam seminggu untuk melakukan perawatan pada anggota atau organ badan yang berbeda. Kehidupan cintanya dengan Lucrecia di dunia lebih kepada imajinasi daripada kenyataan, apa yang dia ingin adalah berada dari apa yang sebenarnya dia. Dia selalu terjebak dalam mimpinya, yaitu dengan membayangkan hal-hal erotis dari beberapa media dan mereka dapat mendukung fantasi seksualnya. Don Rigoberto memaksa istrinya untuk berhubungan seks dengan laki-laki lain dan hal itu sangat mengejutkan istrinya.Faktanya adalah bukti bahwa Don Rigoberto mendapatkan kepuasan melalui obsesinya. Kata kunci: sexuality, fantasy, desire, anxiety, psychological trauma Introduction Human cannot be separated with needs. There are three basic drives such as eating, sleeping, and sex. As a normal human being, sexuality is given from the beginning ourselves. Nietzche asserts that “we are not only rational out being, but we are also full of desire, with the drives and hidden longing, which formed, our ideas and views about the world” (O’Donnel, 2008: 41).In reality, sexuality describes a huge range of activities. This is half of dialectic, anything can be sex because sex has whatever meaning human experience moment by moment, and sex hasan infinite range of meanings because the scope of activities that can properly be called sexual is so vast. Lisa Downing says that sexuality is something that we ourselves create-it is our own creation, and much more than the discovery of secret side of our desire. Sex is not fatally, it is possible to creative life (Downing 2008:104). Sex can make people different. It means that sex is created because of love, relationship, and perhaps necesity or situation. Sex is not taboo anymore in this modern era, but sex can help viability in science. In psychoanalyticterms, sexuality plays an enormously influential rolein psychological development.From a veryearly age, how people experience their bodies in relation to the physical world as well as to the internal stimuli and feelings their bodies generate profoundly effects how they view the world and themselves.In particular,conscious and unconscious fantasies are about human’s bodies and sexuality influence the development of stable patterns of sexual identity, and with that,sexual behaviors.(http://psychoanalysis101.org/psycho-sexual-development/). Sexual fantasies play a central role in mental life, despite – or rather: because of – the fact that they in particular meet the fate of repression, which is why Freud calls them “the weak spot in our psychical organization” (Freud, 1911: 223). This repression creates the psychic disposition towards neurosis in man, the conflict between unconscious desires and conscious control. That sexuality is actually the weak spot in man’s psychical organization is proven by the fact that many (predominantly male) users of the Internet cannot resist the temptation to seek sexual pleasure via the computer screen. Sex is still the biggest business on the net, offering such a massive electronic hallucination of gratifying objects. In Praise of the Stepmother with Mario Vargas Llosa as the author, Mario Vargas Llosa, which reached worldwide recognition with his novels Pantoja and the Special Aunt Julia and the Scriptwriter, The War of the Worlds.In Praise of the Stepmother, made a foray into a genre that is emerging in many of his works, the erotic. Sex in the novels may offend, amuse, or worse. As this study has come toexpect of VargasLlosa as the author of this novel, he uses a precisely structured form to present the distinct components of his story. Structure can be invaded or skewed which is an interesting way to make point innocence and morality are strong themes which are compound in unusual ways. In Praise of the Stepmother with Mario Vargas Llosa as the author, Mario Vargas Llosa, which reached worldwide recognition with his novels Pantoja and the Special Aunt Julia and the Scriptwriter, The War of the Worlds.In Praise of the Stepmother, made a foray into a genre that is emerging in many of his works, the erotic. Sex in the novels may offend, amuse, or worse. As this study has come toexpect of VargasLlosa as the author of this novel, he uses a precisely structured form to present the distinct components of his story. Structure can be invaded or skewed which is an interesting way to make point innocence and morality are strong themes which are compound in unusual ways. Mario Vargas Llosa was born in Arequipa, the second city of Peru, in March 1936.In 1958 he travelled to Paristhanks to a prize won in a short story competition,and on his return to Lima he completed his higher education and received a grant to transfer to theUniversity of Madrid. A few months after arriving in the capital of Spain,he left his studies for the doctorate and settled in Paris, where he was to stay for seven years.In 1963 he published his first great novel, "La ciudad y los perros", with which he won several literary prizes, among them the "BibliotecaBreve" and "La Crítica".It has currently been translated into more than twenty languages. His second major work wastobe"La Casa Verde",published in 1966, the same year he moved to London, wherehewould teach at the university and contribute frequently to newspapers and magazines.Afterwritingone of his fundamental novels, "Conversación en la catedral", VargasLlosatravelled to Barcelona in 1970, where he was to stay for almost five years until in 1974 he put an end to his European exile and returned to Peru with the intention, for the first time, of settling down there. In 1973, his novel Pantaleóny lasvisitadoras, which was adapted for the cinema two years later, had come out.In 1975 he began a seriesof projects related with the cinema and in March of that year he was elected as numerary member of the Peruvian Academy of the Spanish Language. Two months later, he was appointed as president of Pen Club International, a post which he would hold until 1979. Mario Vargas Llosa began his political activity in 1987, due to the nationalization of thefinancial system in Peru. As candidate for the presidency of his country in 1989 with the centre-right coalition Frente Democrático, he was finally defeated in the ballot by Alberto Fujimori. Apart from the works mentioned above, the following works may be highlighted among the output of Mario Vargas Llosa: the novels "La tía Julia y el escribidor" (1977), "La Guerra del fin del mundo" (1981), "Historia de Mayta" (1984), "Quiénmató a Palomino Molero?" (1986), "El hablador" (1987) and "Elogio de la madrastra" (1988); in his facet as a playwright he has written "La señorita de Tacna" (1981), "Kathie y el hipopótamo" (1984) and "La Chunga" (1986) and as an essayist he has published important works such as "GarcíaMárquez: historia de un deicidio" (1971) and "La orgíaperpetua:Flauberty Madame Bovary" (1975).”In Praise Of The Stepmother” (1988). Mario VargasLlosa was a conservative candidate (Fredemo, the Democratic Front) for the Peruvian presidency in 1990.The development of his political convictions, from a sympathizer of Cuban revolution to the liberal right, has astonished his critics and has made it impossible to approach his work from a single point of view. Sabine Koellmann has noted that the publication of Vargas Llosa's La Fiesta del Chivo (2000, The Feast of the Goat) confirmed, "thatpolitics is one of the most persistent 'demons' which, according to his theory, provoke his creativity." (Vargas Llosa's Fiction & the Demons of Politics, 2002) Vargas Llosa was defeated by Alberto Fujimori, an agricultural engineer of Japanese descent, also a political novice, but who had a more straightforward agenda to present to the voters. Anunexpected twist in the plot of this political play occurred in 2000, when President Fujimori escaped to his ancestral homeland Japan after a corruption scandal. From 1991 to 1992 Mario Vargas Llosa worked as a visiting professorat Florida International University, Miami and Wissdens chafts kolleg, Berlin. In addition to the Nobel Prize, the author has received many other honors. Among other distinctions, he has received the "Ramón Godoy Lallana" Journalism Prize, the LiteraryPrize of the Italo-American Institute, the "Pablo Iglesias "LiteraturePrize, the "Hemingway"Prize, the Gold Medal of the Americas and the Max Schmidheiny Foundation Liberty Prize. Already a classic due to the scope and quality of his work, he is one of the Spanish-American writers who has most consistently and determinedly brought theresources of the 20th century literary avant-garde inour language. In Praise of the Stepmother is one literary work by Mario Vargas Llosa. In this novel, there are found many expressions by the characters Don Rigoberto is an art connoisseur and erotic explorer night by night as well as man obsessively devoted to the care of his own body. Lucrecia as a second wife of Don Rigoberto, she is a beautiful and passionate woman, and then his son Alfonso, known as Fonchito.The first character introduced to us in the novel In Praise of the Stepmother, Vargas Llosa takes on an expedition through the mind of Don Rigoberto, day by day an insurance executive, by night a pornographer and sexual enthusiast. Don Rigoberto is a member of Lima's well-heeled bourgeois society. He is the kind of man one sees at board meetings and cocktail parties. But by night Don Rigoberto sheds his conventional skin to pursue his true passions: erotic art and sexual fantasy. Rigoberto’s love for Lucrecia is an addiction of her body parts, a revere or an objectification of her physical persona. This way of looking at love and people and considers women as their property, rather than primarily enjoying her body is part of her. He loves her as a compilation of body parts. In the novel In Praise of the Stepmother signals the historical endpoint to the popularity of the 1960s liberationist sexuality, especially female sexuality as a carrier of a symbolic charge of social freedom. This novel is a thought-provoking fantasia on innocence, sex, and art. It opens with a portrayal of a liberated sexual woman, Lucrecia, who is adored by her husband, Rigoberto. Don Rigoberto's and Lucrecia's erotic exploits which are modeled after paintings that are actually printed in the book. Through this story, Mario Vargas Llosa explores the ideas of the erotic imagination. Rigoberto creates erotic fantasies, the erotic and sexual lives of Rigoberto and Lucrecia, much of which is driven by Rigoberto’s fantasies formulated from paintings. In this Story, Fonchito seems to corrupt innocence, live a harmonious sexual fantasy with her stepmother. Nothing inhibits them or stops them. Dona Lucrecia and stepson Fonchito are revealed in every detail. There is erotic novel. Sexual Fantasy of Rigoberto, a harmonious sexual fantasy of Alfonso to his stepmother, and sexual attraction Lucrecia to Alfonso. Sexual Fantasy is chosen where this study is taken because of the interesting case and the impact which make the wife had anxiety and psychological trauma. From the reading, the study can be interested in focus on the sexual fantasy experienced by the main character. In the novel In Praise of the Stepmother, this study would like to learn more, how Don Rigoberto’s sexual fantasy. What are the activities of Don Rigoberto’s Sexual Fantasy, what are the factors,the causes and the theory, which is matching discuss those cases istheory of Fantasy of Jacques Lacan, supported theory fantasy of Baron. Many kinds of Sexuality, there are Sexualization, Sexual health and Reproduction. Sexual identity, sensuality and intimacy. Sensuality involves human’s level of awareness, acceptance and enjoyment of men’s own or others bodies. In the circle of sexuality, fantasy is part of sensuality. Sensuality is match with Don Rigoberto’s Sexual Fantasy. In the novelIn Praise of the Stepmother, Many statements which can prove that Don Rigoberto have an extreme sexual fantasy. One night, he said that Lucrecia is his fantasy not his wife. He imagined that Lucrecia is Venus, a person who is his fantasies. For the tittle of my thesis is “Don Rigoberto’s Sexual Fantasy.DonRigoberto has an extreme sexual fantasy, he obsesses of three things: Personal Hygiene, sex with Lucrecia, and erotic paintings. His sexual fantasy actually impact on his wife, according to me that’s so interesting.Because of those, thus this study directed to more examine about Don Rigoberto’s sexual fantasy. In analyzing Don Rigoberto’s sexual fantasy and Don Rigoberto’s sexual fantasy impact on his wife, it is used some related concept and two theories. In this thesis, the problem statement is divided into two. The first problem statement deals with Don Rigoberto’s sexual fantasy reflected in this novel. While the second problem deals with How does Don Rigoberto’s sexual fantasy impact on his wife in Mario Vargas Llosa“In Praise of the Stepmother. Those problems can be analysed by using the theory fantasy of Jacques Lacan, supported with Baron and also using concept of anxiety and psychological trauma. The first statement is how Don Rigoberto’s sexual fantasy reflected in In Praise of the Stepmother. This statement will use theory fantasy of Jacques Lacan and suppoeted with theory fantasy of Baron. Through fantasy, the subject attempts to sustain the illusion of unity with the other and ignore his or her own division. Fantasy originates in “auto-eroticism” and the hallucinatory satisfaction of the drive. Fantasies are the way in which subjects, structure or organize their desire: it is the support of desire. Then the second statement isHow does Don Rigoberto’s sexual fantasy impact on his wife in Mario Vargas Llosa“In Praise of the Stepmother. This statement will also apply the theoryof fantasy of Jacques Lacan and also apply the concept of anxiety and psychological trauma. Actually, there are two impacts of Don Rigoberto’s sexual fantasy. Methods Research methodolgy that used in this analysis here must be qualified as an applying in literary appreciation. The thesis is regarded as a descriptive-qualitative study and uses a library research..The data obtained to answer research question study. This study uses novel of Mario Vargas Llosaentitled In Praise of the Stepmother that published in 1988 as the data source of this study. The datas are in the form of direct and indirect speech of the characters, dialogues, epilogues and quotations which indicate and represent aspect of infidelity and love and will which is experienced by the main character. This thesis is using the library method in collecting the data. It does not use the statistic method. That is why it is not served in numbering or tables. Library research used an approach in analyzing this study. The kind of library research which is used here is intensive or closely reading to search quotations or phrases. It also used to analyze the literary elements both intrinsic and extrinsic. The references are taken from library and contributing ideas about this study from internet that support the idea of analyzing. Some steps of how the data is analyzed will be described as follows: Classification based on the statement of the problems. This classification is used to avoid the broad discussion. There are two classifications in this study. They are sexual fantasy and the main factor that lead to his sexual fantasy. Describing Don Rigoberto’s sexual fantasywhich is stated from the quotations or statements by using theory of fantasy to be applied to the data.Describing Don Rigoberto’s sexual fantasy impact on his wife which is stated from the quotations or statements by using theory of fantasy and the concept of anxiety and psychological trauma will to be applied to the data. RESULT 3.1 Reflection of Don Rigoberto’s Sexual Fantasy Based on theory of fantasy of Baron, fantasy can be a kind of activity that permits the subject to escape, however briefly from the stresses and boredom of the subject’s life. Schaefer and Millman support this theory by stating that fantasies provide “a strong feeling of satisfaction in comparison to the bedroom of everyday activities” as an escape of the continued failure of difficulties in their everyday life”. (Baron, 1995: 31-32) Fantasy is used as an escape from responsibility or a harsh home or work situation. Then the person needs to begin to pray for favor on the job or at home, asking God to open hearts to each other's needs and binding out demonic forces. We have had great reports from this kind of prayer. Then as the stress is lifted and the relationships are made stronger, the desire to escape lifts as well. The fantasies are no longer a problem. 3.1.1.1 Fantasy escape Don Rigoberto from stresses and boredom of his life Don Rigoberto is the dull though the prosperous manager of a Lima insurance company. His life represented in the eyes of others, that routine existence as the general manager of an insurance company, he has many activities. Well-earned that he stress or bored with some of his activities as an insurance executive. He had found in his solitary hygienic practiced and all in the love of his wife appeared to him to be sufficient compensation for his normalcy. He creates erotic fantasies, and Lucrecia lives out the character she has been chosen to be. “Just a pinch of wisdom to use as a momentary antidote to the frustrations and annoyances that seasoned existence. He thought: Fantasy gnaws life away, Thank God” (Llosa, 1988: 104) From the statement above, Rigoberto seems like indeed the power of wisdom can be used as a momentary antidote to the frustrations and annoyances that seasoned existence, but it just can be a momentary antidote now the make frustrations and annoyances gnaws away. As a manager of a Lima insurance company, it is definitely that he has 1many activities so he needs something which can release him from the frustrations and annoyances. The word “Fantasy gnaws life away, Thank God”, it shows that Don Rigoberto thinks that fantasy helped him out of the frustrations and annoyances thing which is part of being an insurance executive. He was thankful, fantasy make he enjoyed or even suspected as happiness. There is proof that Fantasy can escape from the stresses and boredom of life “[....] as though happy to rid itself of the policies and the detritus of the day’s bussiness.Ever since, in the most secret decision of his life-- so secret that probably not even Lucrecia would ever be privy to it in its entirity-he had resolved to be perfect for a brief fragment of each day. (Llosa, 1988: 54) Rigoberto is obsessed with Personal Hygiene, he assumes that is the part of his sexual fantasy to get pleasure. According to him, the nightly ritual can as a though happy to a rid himself from detritus bussiness day. He had resolved to be perfect for a brief fragment of each day through nightly ritual. 3.2 Don Rigoberto’s Sexual Fantasy impact on his wife In the novel In Praise of the Stepmother, Don Rigoberto focuses so completely on hisrich fantasy life - a fantasy life,multiplyed by his reproductions of smutty nudes by the likes of Titian and Jordaens (left), that he doesn't notice the risks that cause Dona Lucrecia anxiety. In this novel, there is no communication between Don Rigoberto and Dona Lucrecia about sexual fantasy, Don Rigoberto's intend for his wife disrupts into his fantasies—at times he is too impaired by sorrow and desire to go on. “The queen sometimes awakens at night, overcome with terror in my arms, for in her sleep the shadow of the Ethiopian has once again burst into flame on top of her.” (Llosa, 1988: 20) This quotation above describes that Lucrecia feels anxiety, she always pictured events that foregoing Don Rigoberto forced Dona Lucrecia sex with Atlas, Don Rigoberto assumes that Atlas is the best endowed of his Ethiopian slaves. It can be explained through this statement : “One night-I was drunk-I summoned Atlas, the best endowed of my Ethiopian slaves, to my apartments, merely to confirm that this was so. I had Lucrecia bow down before him and ordered him to mount her.Intimated by my presence, or because it was too great a test of his strength, he was unable to do so. Again and again I saw him approach her resolutely, push, pant, and withdraw in defeat” (Llosa, 1988: 15) Fantasy is 'that thing is what can satisfy me' – objectivation of desire.This line of thought on perverse fantasy, that fixates desire onto a certain object and thus screens off from its infinity, make the interpretations understandable From the quotation above Don Rigoberto was fantasized and forced his wife into having sex with Atlas. There looks Rigoberto so rude to treat his wife, he made his wife as an object because he wanted to prove whether Atlas, the best endowed of my Ethiopian slaves can equals him and he merely to confirm that this was so. The Fantasy that is shown by Don Rigoberto occurs when he decided his wife sex with Atlas. Don Rigoberto feels satisfied and relieved after that incident. Because of that incident, he discovered that no one can equal him. Butitis notperceivedby Lucrecia, she feels not enjoy. “In order to fulfill my part of the offer, we were obliged to act with the greatest discretion. That episode with Atlas, the slave, had been deeply shocking to my wife. (Llosa, 1988: 19) In the statement above, He has also realized that the episode with Atlas makes Dona Lucrecia shock. In contrast, Don Rigoberto does not appreciate his wife. He just concerned with his fantasy and never regards Dona Lucrecia’s pleasure. There is no communication between Don Rigoberto and Dona Lucrecia about sexual fantasy, Rigoberto just concerned with his fantasy and Dona Lucrecia only silent to face it. She did not attempt to revolt or reject command from her husband She never stated that she does not enjoy it. She feels anxiety until it can be said that she have psychological trauma. Lucrecia always awakens at night just because it was too painful for her. For Lucrecia it would be a deeply shocking. In the chapter twelve, Labyrinth of Love.Lucrecia expresses her feelings that she felt as fortunate victim, she just an inspiration. Until there show that she fantasized with herself “I know this because I have been the fortunate victim; the inpiration, the actress as well [.......]. Myself, erupting and overflowing beneath your attentive libertine gaze of a male who has officiated with competence and is now contemplating and philoshopizing (Llosa,1988: 118) It shows that Dona Lucrecia feels that she just an actress who serve her husband for being another person, not being herself while they having sex. She was erupted and overflows, she wants to vent all her anxiety. Until she actually made masturbation to gained the power of magic, mystery and bodily enjoyment. “That woman is what I am, slave and master, you offering. Slit open like a turtledove by love’s knife: I: cracked apart and pulsing. I:slow masturbation. I: flow of musk. I: labyrinth and sensation. I: magic ovary, semen, blood, and morning dew.That is my face for you, at the hour of the senses. I am that when, for you, I shed my everyday skin and my feast-day one. That may perhaps be my soul. Yours.” (Llosa, 1988: 119) In the statement above, it is clear that Lucrecia uncomfortable with the sexual fantasy of his husband. She even feels the pleasure through masturbation. Because throughon masturbation, she could be herself, not as an actress or inspiration of her husband. Conclusions This last chapter is drawn to sun up the results of the analysis, which is presented in the form of summary. In this chapter, the conclusion will be divided into two, in line with the statement of problem. The first conclusion in terms of Don Rigoberto’s sexual fantasy. For the second conclusion is Don Rigoberto’s sexual fantasy impact on his wife. From the analysis that has been in the previous chapter, it can be conclude in the first conclusion that Don Rigoberto obsessed with three things, they are personal hygiene, sex with his wife and erotic paintings. Based on Don Rigoberto’s it is found out that there are many habits and factors which are espouse his sexual fantasy. Besides, his character is his sexual fantasy done for his pleasure and cause of his desire. As aLima manager insurance, Rigoberto definitely has many activities, multiple frustrations and annoyances. So, the fantasy can help to escape him from that. In this study also reveal that Fantasy can make Rigoberto to be wise. He had rediscovered that wisdom all by himself, on his own and at his own risk. He did many habits like imagining erotically things about the media then sets the intent of those media into his mind.He reduces his wife as an object. He determines himselfbecome someone who is in the media, he proud of person in the paintings which can inflame his subject’s imaginings then he changes himself as that person. In the novel In Praise of the Stepmother learn of the erotic and sexual lives of Rigoberto and Lucrecia, and which is driven by Rigoberto’s fantasies formulated from paintings and other media. He showers her with affection, but the reader is left wondering if he truly knows her, or if he has created an illusion of her. Don Rigoberto’s Sexual Fantasy happened because of any media, and he enjoyed his sexual fantasy by any media, like painting, poet and tried to take it into his mind, then reveal to his wife. His love life with Lucrecia in a world more imaginary than real, of what he wishes she were than what she really is. Don Rigoberto assumes that his wife is like another person who is in his mind, not the realism of his wife’s self. He always lost in his dream which is imagined erotically things from some media and those can support his sexual fantasy. Don Rigoberto is compulsive about his personal cleanliness and his bodily functions. He appreciates them as impressive and necessary. He devotes a day a week for the care of a different member or organ: Monday, hands; Tuesday, feet; Wednesday, ears; Thursday, nose; Friday, hair; Saturday, eyes; Sunday, skin. Don Rigoberto is a sensualist of the highest order and, nightly, he and his wife have erotic heights. He did nightly ritual,all of those are the parts of his sexual fantasy. The pictures and roses of the painting are as an inspiration for him while having sex with his wife. Sexual fantasy can have a profound impact on a person’s emotions. Sexual fantasy is articulated with anxiety and it is closest proximity to the psychological traumatic real, Lucrecia always be object of Rigoberto’s sexual fantasy, she forced sex with Atlas, the best endowed of Ethiopian slaves. It shows that Don Rigoberto never worried about Lucrecia’s anxiety. He actually lets Lucrecia having sex with another man, just for create pleasure Dona Lucrecia as his wife feel that she just an actress who serve her husband for being another person, not being herself while they having sex. She actually made masturbation to gained the power of magic, mystery and bodily enjoyment. She also did sexual attraction to her stepson, Fonchito. Because while having sex with her stepson, she feels splendid orgasm she is to be herself, she felt the pleasure and comfort thats he never got while having sex with Rigoberto, with Foncho, she feels that he is innocence and not seems like Rigoberto who makes she is an object imagination of anyone and object for him to get sexual satisfaction and pleasure. Don Rigoberto can do sexual fantasy to his wife because of his desire, he obsessed of personal hygiene,erotic paintings, then he makes his wife become the object of his fantasy and he wants to get pleasure which can alter his mood to be happy. The act of Don Rigoberto that forced his wife with another man can be classified as sexual violence which is the cause of psychological trauma. So, with the sexual fantasy of Don Rigoberto can impact Lucrecia has psychological trauma. Refferences Allen, Richard. 1995. Projecting Illusion. Film Spectatorship and the Impression of Reality. Cambridge: Cambridge University Press. Badiou, Alain. 2012. In Prasise Of Love. London: Serpent’s Tail Baron, Robert A. 1995. Psychology, 3rded. Boston: Allyn and Bacon. Bernet, Rudolf. 1996. Verbeelding en fantasma. In: A. Vergote, and P. Moyaert, eds. Psychoanalyse. De mens en zijn lotgevallen. Kapellen: DNB/Pelckmans, 171-183. Byrne, D. 1977. The imagery of sex. In J. Money & H. Musaph (Eds.), Handbook of sexology .Amsterdam: Elsevier, pp. 327-350. Camassa, G. 1989. Phantasia. Historisches Wörterbuch der Philosophie Band 7, Basel: Schwabe & Co., 516-534 Deutsch, J. 1944. The psychology of women. New York: Grune & Stratton. Doskoch, P. 1995. The safest sex. Psych. To.28:46-9 Downing, Lisa. 2008. The Cambridge Introduction to Michel Foucault. New York: Cambridge University Press. Evans, Dylan. 2006. An Introduction Dictionary of Lacanian Psychoanalysis. Taylor & Francis e-Library. Foucault, Michel. 1978. In The History Of Sexuality Vol 1. Trans. Robert Hurley.New York: Pantheon Books. Freud, Sigmund. 1908. Hysterical Phantasies and their relation to Bisexuality. S.E. 9, pp 159-166. Freud, Sigmund. 1911. Formulations on the Two Principles of Mental Functioning. S.E . 12, pp 218-226 Freud, Sigmund. 1955. Journal Pastoral Psychology. Kluwer Academic Publishers, 6, pp 43-41. Freud, Sigmund. 1962. Creative writers and daydreaming. In J. Strachy (Ed.), The standard edition of the complete psychological works of Sigmund Freud,9, 142-152). London: Hogarth. (Original work published 1908) Freud, Sigmund. 1979. From The History of an Infantile Neurosis. London: Penguin Books. Freud, Sigmund. 1989. Introductory Lectures On Psychoanalysis. New York: W. W. Norton & Company. Gagnon, J. H., & Simon, W. 1973. Sexual conduct. Chicago: Aldine. Garrison, Karl C. And Dewey G. Force, Jr. 1965. The Psychology of ExceptionalChildren Fourth Edition. The Ronald Press Company. Gerbner, George, Catherine J. Ross, Edward Ziggler. 1980. Child Abuse an Agenda for Action. New York: Oxford University Press. Gerrig, Richard. J. 1996. Psychology and Life. 14th ed. New York: Harper Collins Publisher. Giambra, L. 1974. Daydreaming across the life span: Late adolescent to senior citizen. International Journal of Aging and Human Development,5, 115-140. Hicks, T.V., and H. Leitenberg. 2001. Sexual Fantasies About One’s Partner Versus Someone Else: Gender Differences in Incidence and Frequency. Jour. Sex Res, 38:43-51. Hollender, M. H. 1963. Women's fantasies during sexual intercourse. Archives of General Psychiatry, 8, 86-90. Homey, K. 1967. Feminine psychology. New York: Norton. Hurley, Robert. 2011. The Limits of Ferocity: Sexual Aggression and Modern Literary Rebellion. New York: Duke University Press Books. Jones, J. C, & Barlow, D. H. 1990. Self-reported frequency of sexual urges, fantasies, and masturbatory fantasies in heterosexual malesand females. Archives of Sexual Behavior, 19, 269-279. Kaplan, H. S. (1974, October). Fiction and fantasy: No-nonsense therapy for six sexual malfunctions. Psychology Today, pp. 77-86. Kartono, Kartini and Dadi Gulo. 1987. Kamus Psikologi. Bandung: Pionir Jaya. Lacan, Jacques. 1994. The Seminar, Book III .1955-1956. The Psychoses, ed. by Jacques Alain Miller,trans. by Russell Grigg. New York: Norton. Lacan,Jacques. 1978. Four Fundamental Concepts Of Psychoanalysis. New York: W. W. Norton & Company. Lacan, Jacques. 2005. Routledge Critical Thinkers Book. New York: Routledge. Laplanche, J.1986. Fantasy and the Origins of Sexuality, London: Routledge. Le Séminaire XIII: L’objet de la psychanalyse. 1965-1966. Unpublished transcript. Le Séminaire XIV: La logique du fantasme 1966-1967. Unpublished transcript. Meadows, Robert J. 2004. Understanding Violence and Victimization Third Edition. New Jersey: Prentice Hall. Miller, Jacques-Alain. 1999. Les six paradigms de la jouissance. La CauseFreudienne, 42: 7-29. Nobus, Dany. 2002. Jacques Lacan and the Freudian Practice of Psychoanalysis. Taylor & Francis e-Library. Nusselder, André. 2006. Interface Fantasy. Amsterdam. F&N Eigen Beheer. Pp 117. O’Donnell, Kevin. 2008. Postmodernisme. 1st ed. Yogyakarta: Kanisius. Reich, W. 1942. The discovery of the orgone: The function of the orgasm. New York: Noonsday. Rogers, Dorothy. 1969. Child Psychology. Belmont, California. Wadsworth Publishing Company,Inc Singer, J. L. 1966. Daydreaming: An Introduction to the experimental study of inner experience, New York: Random House. Singer, J.L. 1968. Research applications of the projective methods: In A. Rabin (Ed.), Projective techniques in personality assessment. New York: Springer. Suryabrata, Sumadi. 2002. Pengembangan Alat Ukur Psikologis,Yogyakarta: Penerbit Andi Yogyakarta. ---. The Seminar, Book X. 1962-1963. Anxiety, ed. By Jacques Lacan, trans. by Cormac Gallagher. French: Unedited manuscript. ---. The Seminar, Book XI. 1981. The Four Fundamental Concepts of Psycho-Analysis, ed. by Jacques Alain Miller, trans. by Alan Sheridan. New York: Norton.. ---. The Seminar, Book XX 1972-1973, Encore, ed. by Jacques Alain Miller, trans. by Bruce Fink. New York: Norton. Vargas Llosa, Mario. 1988. In Praise Of The Stepmother. New York: Picador. Wagman, M. 1967. Sex differences in types of daydreams. Journal of Personality and Social Psychology, 7, 329-332. Wilson, G.D. 1997. Gender Differences in Sexual Fantasy: An Evolutionary Analysis. Person. Individ. Diff, 22, 27-31. Žižek, S. 1992. Looking Awry. Cambridge Massachusetts: MIT Press. Internet Sources . http://classiclit.about.com/od/literaryterms/g/aa_whatisliter.html http://psychoanalysis101.org/psycho-sexual-development/html http://www2.ucsc.edu/dreams/Library/hall_1953b.html http://www.sparknotes.com/psychology/psych101/motivation/section3.html http://www.bartleby.com/288/5.html http://www.personalityresearch.org/papers/plaut.html